2015
DOI: 10.5455/2319-2003.ijbcp20150205
|View full text |Cite
|
Sign up to set email alerts
|

Study of effects of metformin on C-reactive protein level in Type-2 diabetes mellitus

Abstract: Background: Diabetes mellitus (DM) is extremely common; represent a significant global health problem. Type-2 DM is considered to be associated with a low grade inflammation, which may play a significant role in development of cardiovascular complications evidenced by C-reactive protein (CRP) is a an extremely sensitive marker of systemic inflammation. The study was undertaken to check the effect of metformin on CRP level in Type-2 DM. Methods: The study was prospective and non-randomized. Thirty newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Table 1 details the baseline characteristics of the 13 studies included in the meta-analysis. 15-18,26-34 A total of 13 articles representing 1776 participating patients with IGT and T2D were detected as appropriate literature for this meta-analysis. The study by Mo et al 26 was separated into 3 studies because they included different metformin treatment durations and dose levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 details the baseline characteristics of the 13 studies included in the meta-analysis. 15-18,26-34 A total of 13 articles representing 1776 participating patients with IGT and T2D were detected as appropriate literature for this meta-analysis. The study by Mo et al 26 was separated into 3 studies because they included different metformin treatment durations and dose levels.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis indicated that the removal of 2 studies (Gamit et al 34 and Mo et al 26 ) with low quality by means of "leave-one-out method" from the analysis of CRP ([SMD = −0.78 mg/L; 95% CI = −1.53, −0.027; P = 0.04), TNF-α (SMD = 0.09 mg/L; 95% CI = −0.52, 0.71; P = 0.77), and IL-6 (SMD = 0.18 mg/L; 95% CI = −0.52, 0.90; P = 0.60) did not change the results of the current pooled analysis for circulating levels of CRP, TNF-α, and IL-6 (Figure 3). Forest plot evaluating standardized mean difference (SMD) and 95% CIs for the impact of metformin treatment on circulating levels of (A) C-reactive protein, (B) tumor necrosis factor-α, and (C) interleukin-6 in patients with T2D.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Metformin has further been shown to reduce measures of adiposity among overweight and obese adolescents with type 1 diabetes ( 88 ), to inhibit androgen biosynthesis ( 89 , 90 ), and to reduce inflammatory markers such as hsCRP and IL-6 ( 91 93 ). The anti-inflammatory medication Celecoxib may also be a promising adjunct as it has been found to promote an accelerated treatment response among acutely ill patients at early illness phase ( 18 ).…”
Section: Bsd Treatment In Youth: Sgas Are Considered First Line Treatmentioning
confidence: 99%
“…Since the previous studies investigated the role of the antidiabetic drug on inflammatory process, type-2 Diabetes Mellitus patients showed a decreased level of CRP after taking the metformin. 10 Overall, metformin plays a crucial role to reduce the CRP concentration which contributes to reduce the inflammation and prevent the development of cardiovascular complications. 11,12 Negligible inflammation can trigger classical pathway of the complement system, which is composed of subunits protein found in the blood.…”
Section: Introductionmentioning
confidence: 99%